THE IMPACT OF THE FINANCIAL PERFORMANCE RATIO AND SHARES PRICES ON THE INDONESIAN STOCK EXCHANGE IN THE LQ45 INDEX - Hengky Leon (SEAN Institute, 2023)
The aim of this research is to analyze ratios which include Current Ratio (CR), Debt Equity Ratio (DER), Return on Equity (ROE), and Financial Performance which includes Earning per Share (EPS), have an impact on IDX stock prices. Companies included in the 2015-2016 LQ45 index will be studied further in this study. Purposive sampling was used to select the sample for this study, with 56 companies selected based on the sample obtained in this study. (1). The current ratio has a beneficial effect on stock value, according to the findings. (2). Share prices are not affected by the debt to equity ratio. (3). Stock prices are not affected by Return on Equity. (4). Earnings per share have a beneficial impact on the stock market.